Repeated measurements of in vitro fermentation of fibre‐rich substrates using large intestinal microbiota of sows. (30th August 2012) - Sappok, Maria A; Pellikaan, Wilbert F; Verstegen, Martin WA; Bosch, Guido; Sundrum, Albert; Hendriks, Wouter H
Abstract BACKGROUND: Fibrous ingredients for pig diets can be characterized by in vitro fermentation. In vitro fermentation methods often use a one‐time measurement of gas production during the incubation of test substrates with one faecal inoculum. The representativeness of this approach can be questioned as measuring time and number of animals from which inoculum originates may influence fermentation results. An in vitro fermentation trial was conducted incubating three fibrous substrates with three inocula in five replicates (different fermentation runs) to test the influence of run and origin of inocula. RESULTS: Total gas production and maximal rate of gas production differed (P < 0.05) between fermentation runs, but less than substrates (P < 0.01). The ranking order between substrates remained similar for each run. Fermentation of cellulose led to higher coefficients of variation between inocula compared to the fast fermentable substrates oligofructose and soy pectin. Differences ranged from 2% for total gas production up to 25% for maximal rate of gas production. CONCLUSION: One fermentation run can provide representative results for substrate ranking. Using multiple inocula mixed from four faecal samples each leads to high coefficients of variation for slow fermentable substrates like cellulose. Future studies should examine the optimal number of animals for inocula preparation to decrease variation. © 2012 Society of Chemical Industry